Electrospun Nanofibers In Wound Care: Mechanistic Insights And Therapeutic Perspectives - Fareed, G.Mohamed Shaik; Devi, Akila (Journal of Neonatal Surgery, 2025)
Tissue injury is more common than before,and it requires innovative tissue engineering and regenerative medicine strategies. In this work, egg yolk oil-infused electrospun nanofibers were developed and characterized for the potential applications as scaffolds in the tissue engineering domains. Because of their relatively large surface area and their ability to mimic the extracellular matrix, electrospun nanofibers have great potential as substrates for cell adhesion and proliferation. Widely used in the biomedical area and tissue engineering, the addition of egg yolk oil (bioactive components as phospholipids and antioxidants), enhances nanofiber structure at mechanical and biological level. These features allow for the controlled release of bioactive molecules, accelerating cell proliferation and tissue recovery. The findings highlight the enhanced biocompatibility and regenerative potential of egg yolk oilinfused nanofibers in areas such as wound healing, bone regeneration, and nerve regeneration. While formulation stability and regulatory issues may limit its application, this method could be a promising avenue in creation of tissue constructs and should be explored, to optimize these nanofibers and implement them, further inclinic